Pengaruh Return On Asset (ROA), Dividen Payout Ratio (DPR) dan Earnings Per Share (EPS) Terhadap Return Saham pada Perusahaan Sektor Perindustrian yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2020-2022 - Imas Nurika; Endang Dwi Wahyuningsih; Dimas Adi Wicaksono (Jurnal Ekonomi Manajemen Akuntansi, 2024)
Stock returns are one of the indicators in investor investment decision making. Factors that influence stock returns are internal (fundamental) factors, namely ROA, DPR and EPS. The purpose of this study was to determine: the effect of Return On Asset (ROA) on Stock Returns, the effect of Dividend Payout Ratio (DPR) on Stock Returns, and the effect of Earnings Per Share (EPS) on Stock Returns in Industrial Sector companies listed on the Indonesia Stock Exchange in 2020-2022. The data analysis method used is multiple linear regression analysis. Findings: Return On Asset (ROA) has a positive and significant effect on Stock Returns, Dividend Payout Ratio (DPR) does not affect Stock Returns, and Earnings Per Share (EPS) does not affect Stock Returns. The implication of this study for investors is that they can use ROA as the main indicator in analyzing potential opportunities to gain profit from capital gains from stock returns before making investment decisions. The implication for management is to focus on strategies to optimize the use of assets to generate greater profits. Meanwhile, the implications for regulators and policy makers are to encourage transparency in financial reports and the preparation of capital market literacy programs.